Performance analysis and taguchi approach on wire cut EDM using microwave sintered chromium composite. (2021) - Girisha, L; Sridhar, S.; Tadepalli, Lakshmi Deepak; Swetha, M.; Subbiah, Ram; Marichamy, S.
Abstract: In present days, metal industries have meet with high demand of advanced materials with good substance properties such as hardness, toughness and strength. These advanced materials were operating under conventional machining was challenging process and it was difficult due to its excellent hardness. Hence, Wire cut Electrical Discharge Machining (WEDM) process was considered for cutting of Titanium nitride (TiN) reinforced with chromium composite which was produced through microwave sintering process. It was operated under WEDM with the help of input factors such as open voltage, wire feed and tension. Based on the input factor, Surface Roughness (SR) was measured and it was optimized through taguchi technique. The factor contribution was studied through variance analysis.